Oxidative Dissolution of Metals in Organic Solvents - Li, Xiaohua; Binnemans, Koen (Chemical reviews, 2021)
Dissolution of metals in organic solvents is relevant to various application fields, such as metal extraction from ores or secondary resources, surface etching or polishing of metals, direct synthesis of organometallic compounds, and separation of metals from other compounds. Organic solvents for dissolution of metals can offer a solution when aqueous systems fail, such as separation of metals from metal oxides, because both the metal and metal oxide could codissolve in aqueous acidic solutions. This review critically discusses organic media (conventional molecular organic solvents, ionic liquids, deep-eutectic solvents and supercritical carbon dioxide) for oxidative dissolution of metals in different application areas. The reaction mechanisms of dissolution processes are discussed for various lixiviant systems which generally consist of oxidizing agents, chelating agents, and solvents. Different oxidizing agents for dissolution of metals are reviewed such as halogens, halogenated organics, donor-acceptor electron-transfer systems, polyhalide ionic liquids, and others. Both chemical and electrochemical processes are included. The review can guide researchers to develop more efficient, economic, and environmentally friendly processes for dissolution of metals in their elemental state.